The voices of Coriolanus: merit, law, and necessity - Landis, C (2023)
Did Shakespeare argue on ‘both sides’ of questions and stand aloof from political debates? Attempts to locate political sympathies and inclinations have elicited complaints about reducing the plays to their politics; as Jason Scott-Warren cautioned, ‘the attempt to introduce philosophical abstractions’ threatens to ‘extinguish the energies of theatrical narrative’. This thesis explores how Shakespeare orchestrated a diversity of voices to create suggestive patterns of political argument, which are individually unobtrusive but develop an undeniable collective force. Instead of seeking to extract coherent doctrines from the plays, this thesis follows the clusters of proverbs, idioms, key terms, and maxims regularly associated with a wide range of political and social arguments. The modest scale of these discrete elements allowed significant ambiguities: whenever a developing pattern threatened to impose an unwelcome ideological closure, Shakespeare simply disengaged or snagged the thread.